Animal–Visitor Interactions in Zoos and Aquariums: A Systematic Review - Ga-Yi Lin; Keith Chi Hui Ng; Eduardo J. Fernandez (Animals)
There is increasing recognition of the importance of human–animal interaction (HAI) research in the assessment of animal welfare. This is partly reflected by the appearance of increasing animal–visitor interaction (AVI) publications in zoos. Early AVI publications primarily focused on primates and the impact of visitors on animals (visitor effects), with most identifying negative welfare impacts. This review aims to identify trends and changes in the key factors of AVIs (e.g., types of interactions measured; taxa studied; welfare impact). Covidence online software and PRISMA were used to screen papers and extract data. A total of 157 papers comprising 314 studies were included. AVI publications have increased in the last two decades, with a large increase in publications since 2020. Most publications have focused on visitor effects, as opposed to the impact of animals on visitors (visitor experiences). Earlier visitor effect studies mostly focused on primates, while more recent studies have primarily focused on non-primate species. Excluding studies categorized as neutral, there were more visitor effect studies with measures focused on negative than positive welfare impacts. However, the last decade and a half has seen a substantial increase in visitor effect studies measuring positive welfare impacts. These results are discussed in reference to growing changes in the types of studies, species, and outcomes measured in AVIs. In addition, we consider the future of AVI research, including a growing need for and consideration of standardized welfare assessments, the increased use of experimental control, and AVIs that equally promote visitor education and positive animal welfare.